Fertilization with biosolids and chemical attributes of soil cultivated with ‘Pêra’ orange - Andreon Viçosi, Karen; de Oliveira Garcia , Giovanni; Zuculoto , Moises; Pinto da Silva Fonseca, Pedro Henrique (Comunicata Scientiae, 2025)
The study aims to evaluate soil attributes cultivated with orange trees and fertilized with biosolid in their first two years of planting. The experimental design used was completely randomized, with six treatments of eight plants. The treatments were based on the source of fertilization and its dose: T0 - 100% of the recommended dose from mineral fertilization (MF); T1 - 50% MF and 50% biosolid (MF + B); T2 - 100% biosolid (100 B); T3 - 115% biosolid (115 B); T4 - 130% biosolid (130 B); and T5 - 150% biosolid (150 B). The cultivar used was ‘Pêra’ D6, grafted onto Citrandarim Índio. Each treatment consisted of a row of eight plants, evaluating the four central plants. Soil samples were collected at 3, 9, 15, and 21 months after planting. The data were subjected to analysis of variance and mean tests. Biosolids at doses of 100%, 115%, and 150% increased phosphorus, calcium, and base sum levels. Fertilization with biosolid did not increase the amounts of micronutrients and heavy metals in the soil (such as Cu and Zn), which remained within safe limits for agricultural use. Thus, the use of biosolid can be a viable and sustainable alternative to mineral fertilization, provided that legal regulations are respected and constant monitoring is carried out to prevent soil contamination. Good management of sewage sludge application is crucial to ensure sustainability and maximize the benefits of this agricultural practice.